(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
The main intention of this paper is to make a first synthesis of the data concerning the conception of the war between the fifteenth century Purépechas. This synthesis is based on the contrast found in archaeological data, -primarily from mortuary contexts, and ethnohistoric- contained in chronicles, dictionaries and pictures. Therefore the symbolism of weapons, the role of war and the sacrifices will be addressed, as well as the tactical aspects and technology. From all these data it is concluded that most of the strategies were not aimed at killing the enemy on the battlefield but their subjugation and subsequent death on the sacrificial stone. To sum up, the final section is an attempt to understand the war not only as a means to feed the deities, but also as a predatory mechanism for exchanging life forces between conflicting groups.